Uji Efektivitas Ekstrak Daun Cengkeh (Syzygium Aromaticum L.) Terhadap Phytophthora Palmivora Penyebab Penyakit Busuk Buah Kakao (Theobroma Cacao L.) - NI LUH PUTU SONIA SAVITA DEWI; DEWA NGURAH SUPRAPTA; I KETUT SUADA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2019)
Effectiveness of Clove Leaf Extract (Syzygium aromaticum L.) againstPhytophthora palmivora the Cause of Cocoa Fruit Rot (Theobroma cacao L.) Cocoa fruit rot caused by Phytophthora palmivora is one of the main diseases that can greatly reduce the yield of cocoa production in the world. Therefore it isnecessary to control the disease in an environmentally friendly way. One of which isusing botanical pesticides. Clove leaf is one of the plants which extract can be usedas a fungicide. This study aimed to examine the effectiveness of clove leaf extract onP. palmivora the cause of cocoa fruit rot. MIC test and colony test was done using 10extract concentrations namely 0,1; 0,2; 0,3; 0,4; 0,5; 0,6; 0,7; 0,8; 0,9; 1,0 and 0,0%(control). The in vivo test uses 6 extract concentrations of 0,5; 0,6; 0,7; 0,8; 0,9; 1,0and 0,0% (control). The results showed the MIC (minimum inhibitory concentration)of clove leaf extract to suppress the growth of P. palmivora was 0.5% which means itis feasible to be used as a botanical pesticide. Under in vivo condition, clove leaf extractinhibited the growth of fungal colonies and infection and can be used as fungicide tosuppress the growth of P. palmivora. The extract concentration of 1% prevented thedamage of cocoa fruit caused by P. palmivora by 100%.